2021
DOI: 10.3390/antibiotics11010027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Testing for Sepsis: A Systematic Review of Economic Evaluations

Abstract: Introduction: Sepsis is a serious and expensive healthcare problem, when caused by a multidrug-resistant (MDR) bacteria mortality and costs increase. A reduction in the time until the start of treatment improves clinical results. The objective is to perform a systematic review of economic evaluations to analyze the cost-effectiveness of diagnostic methods in sepsis and to draw lessons on the methods used to incorporate antimicrobial resistance (AMR) in these studies. Material and Methods: the Preferred Reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Probably, the first study evaluating the cost-effectiveness of PCT was the ProCAP study [ 94 ] showing that the cost of antibiotics plus PCT measurement was significantly higher in the intervention arm. However, the cost of PCT measurement decreased overtime and a recent systematic review and meta-analysis showed that monitoring of PCT was cost saving [ 95 ]. These findings have been challenged by studies with real world data [ 96 , 97 ] showing that PCT monitoring was associated with potential increase in antibiotic days and LOS.…”
Section: Host-response Biomarkersmentioning
confidence: 99%
“…Probably, the first study evaluating the cost-effectiveness of PCT was the ProCAP study [ 94 ] showing that the cost of antibiotics plus PCT measurement was significantly higher in the intervention arm. However, the cost of PCT measurement decreased overtime and a recent systematic review and meta-analysis showed that monitoring of PCT was cost saving [ 95 ]. These findings have been challenged by studies with real world data [ 96 , 97 ] showing that PCT monitoring was associated with potential increase in antibiotic days and LOS.…”
Section: Host-response Biomarkersmentioning
confidence: 99%
“…Previously, few economic analyses in the field of diagnostics for infectious diseases incorporated considerations of AMR [45][46][47]. The relative reduction of AMR in the analysis shows considerable uncertainty and there are some important assumptions to consider when interpreting these results.…”
Section: Fig 4 Development Of Antimicrobial Resistance For Both Scena...mentioning
confidence: 99%